Pathophysiology of Lipid Droplets in Neuroglia - Tina Smolič; Robert Zorec; Nina Vardjan (MDPI AG, 2021)
In recent years, increasing evidence regarding the functional importance of lipid droplets (LDs), cytoplasmic storage organelles in the central nervous system (CNS), has emerged. Although not abundantly present in the CNS under normal conditions in adulthood, LDs accumulate in the CNS during development and aging, as well as in some neurologic disorders. LDs are actively involved in cellular lipid turnover and stress response. By regulating the storage of excess fatty acids, cholesterol, and ceramides in addition to their subsequent release in response to cell needs and/or environmental stressors, LDs are involved in energy production, in the synthesis of membranes and signaling molecules, and in the protection of cells against lipotoxicity and free radicals. Accumulation of LDs in the CNS appears predominantly in neuroglia (astrocytes, microglia, oligodendrocytes, ependymal cells), which provide trophic, metabolic, and immune support to neuronal networks. Here we review the most recent findings on the characteristics and functions of LDs in neuroglia, focusing on astrocytes, the key homeostasis-providing cells in the CNS. We discuss the molecular mechanisms affecting LD turnover in neuroglia under stress and how this may protect neural cell function. We also highlight the role (and potential contribution) of neuroglial LDs in aging and in neurologic disorders.